2022
DOI: 10.1177/01945998221091908
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Predictors of Free Flap Failure

Abstract: Objective Microvascular free tissue transfer is an important reconstructive option for defects of the head and neck. The present study aims to identify preoperative patient- and tumor-specific characteristics, laboratory values, and other risk factors associated with early free flap failure. Study Design Retrospective cohort study of 1070 patients. Setting Head and neck surgical oncology service at a tertiary care center from 2005 to 2019. Methods Demographics, comorbidities, preoperative laboratory values, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(75 reference statements)
6
7
0
Order By: Relevance
“…14 Two recent studies have found an increased risk of flap failure in those with elevated platelets undergoing lower extremity reconstruction and those undergoing head and neck reconstruction. 15,16 In this study of 502 patients undergoing free tissue transfer, our data echo the mixed consensus in the literature but may offer a hypothesis for these findings.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…14 Two recent studies have found an increased risk of flap failure in those with elevated platelets undergoing lower extremity reconstruction and those undergoing head and neck reconstruction. 15,16 In this study of 502 patients undergoing free tissue transfer, our data echo the mixed consensus in the literature but may offer a hypothesis for these findings.…”
Section: Discussionsupporting
confidence: 85%
“…In a large NSQIP analysis, free tissue transfer in the setting of thrombocytosis was found to increase the need for blood transfusions, prolonged hospital stays, and increased reoperations; however, there was no evidence of increased flap failure 14 . Two recent studies have found an increased risk of flap failure in those with elevated platelets undergoing lower extremity reconstruction and those undergoing head and neck reconstruction 15,16 . In this study of 502 patients undergoing free tissue transfer, our data echo the mixed consensus in the literature but may offer a hypothesis for these findings.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, prolonged ischemia time of free aps and subsequent ischemia-reperfusion injury can increase the risk of postoperative complications and eventual ap graft failure, but this study did not include it due to too many missing values of ischemia time. Elevated platelets are a risk factor for thrombosis, and Stevens, M. N. et al found a 2.67-fold increased risk of ap graft failure for every 1-unit rise in platelet count in patients with head and neck surgical free ap grafts, which is consistent with the ndings of Kalmar, C. L. et al who studied the association of thoracic microvascular repair failure with platelet counts in women [26,27] .…”
Section: Signi Cance Of Each Model Factorsupporting
confidence: 67%
“…2,3 However, necrosis can occur if the color of the surgical site (tissue) changes owing to venous thrombosis (54%-57%), arterial thrombosis (20%-43%), or blood vessel flow disturbance (5%-25%). [4][5][6][7][8] In this case, surgery must be performed again, or a limb may have to be amputated. 4 Thus, an attending physician must continuously monitor a patient to prevent this situation.…”
Section: Introductionmentioning
confidence: 99%